Power integrity : measuring, optimizing, and troubleshooting power related parameters in electronics systems - Sandler, Steven M. (McGraw-Hill's AccessEngineering., 2014)
Proven techniques for generating high-fidelity measurements. Power Integrity: Measuring, Optimizing, and Troubleshooting Power Related Parameters in Electronics Systems provides field-tested techniques for producing high-fidelity measurements using the appropriate equipment. The book thoroughly discusses measurement guidelines, test instrument selection and use, connecting the equipment to the device being tested, and interpreting the acquired data. The latest electronics technologies and their impact on measurement are discussed. Detailed photographs, screenshots, schematics, and equations are included throughout this practical guide. Learn how to accurately measure: Impedance, Stability, Power supply rejection ratio (PSRR), Reverse transfer and crosstalk, Step load response, Ripple and noise, Edges, High-frequency impedance.